2008
DOI: 10.1177/0047287508321201
|View full text |Cite
|
Sign up to set email alerts
|

A Strategic Use of the Communication Mix in the Destination Image-Formation Process

Abstract: National tourist offices and tourism stakeholders are challenged to maintain and secure travel markets. Travelers are constantly bombarded with travel marketing messages. Compounding the challenge is a lack of research on effective, efficient, and optimal methods in convincing tourists to travel to a particular destination. To address this literature gap, a questionnaire survey on destination brand image research was conducted on outbound travelers from four major cities, examining their image perceptions of M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0
5

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(47 citation statements)
references
References 21 publications
1
33
0
5
Order By: Relevance
“…Overall, these studies found that the more familiar -through actual visitation or information -people are about a destination, the more positive the image is. In contrast, some studies found that certain information sources can create negative images of a destination (McCartney et al, 2008;Sonmez and Sirakaya, 2002). In any case, these studies demonstrate the fact that familiarity has some effect on the image of a destination.…”
mentioning
confidence: 75%
“…Overall, these studies found that the more familiar -through actual visitation or information -people are about a destination, the more positive the image is. In contrast, some studies found that certain information sources can create negative images of a destination (McCartney et al, 2008;Sonmez and Sirakaya, 2002). In any case, these studies demonstrate the fact that familiarity has some effect on the image of a destination.…”
mentioning
confidence: 75%
“…Most previous studies have widely adopted a content analysis approach for examining travelrelated materials such as questionnaire surveys (Chi & Qu, 2008), tourist operators' websites (Stepchenkova & Morrison, 2008) and publications (McCartney, Butler, & Bennett, 2008). Recently, travel blogs have become an appropriate communication tool for image formation since they include itineraries, comments and opportunities for further information collaboration (Huang, Chou, & Lin, 2010).…”
Section: Travellers' Destination Imagementioning
confidence: 99%
“…It is evident from the research reviewed above that prospective travelers have access to an extensive network of information and that the information search process is likely to expose them to numerous advertising messages. The challenge for attractions and destinations, therefore, is to first create clear messages that stand out from their competitors'; and second, select communication channels that prospective travelers regard as reliable and trustworthy (McCartney et al, 2008). In this regard, one channel often used to disseminate tourism information in Australia is via local and regional visitor information centers.…”
Section: Sources Of Informationmentioning
confidence: 99%